P05 Involving patients in the discussion about results from the National Early Inflammatory Arthritis Audit. (20th April 2020) - Wade, Oliver; Loh, Jack; Withers, Joshua; Fish, Sarah; MacPhie, Elizabeth
Abstract: Background: The National Early Inflammatory Arthritis Audit (NEIAA) has provided the opportunity for rheumatology services to benchmark the care they provide. It provides a mechanism to identify where services can make improvements and to raise awareness about inflammatory arthritis. We felt it important to share our results with patients and involve patients in the discussion about how we improve the service we deliver. This project outlines how we went about doing this. Methods: Data submitted to the NEIAA online tool were downloaded for analysis. This included all patients recruited during the first year of the audit. Results were presented initially to the Rheumatology Multi-Disciplinary Team. Driver diagrams were developed by the team and areas for improvement identified. A patient poster for the waiting area was also developed. This provided information about our performance in the audit and what changes we were looking to make. Results, driver diagrams and the patient poster were then presented to our National Rheumatoid Arthritis Society (NRAS) patient support group at one of their lunchtime meetings. We met again two weeks later with members from the patient group to get feedback on the driver diagrams and patient poster. Results: Results from the first year of the audit demonstrated that there was significant room for improvement across all seven quality standards. Driver diagrams identified areas for improvement across the whole patient pathway. Forty-five patients and carers attended the lunchtime meeting presentation. Patients identified various areas where they could get involved with improving the patient pathway. These included putting up posters in the community to raise awareness about rheumatoid arthritis and running another Rheumatoid Arthritis Awareness Day. Other proposals were to provide more lunchtime meetings to improve understanding about the condition and management and promote aspects of self-management and developing the role of the Expert Patient locally to support newly diagnosed patients. The patient poster received lots of positive comments, it was suggested that we remove any statistics which might cause alarm and be difficult to interpret and to focus on what quality improvements had already happened locally. Conclusion: Involving patients in the discussion has been a fascinating and rewarding experience. Patients have been empowered and their input has been valued. Patients have provided additional suggestions as to how they can get involved to support the service and improve the patient pathway. The patient poster now tells a positive story and acknowledges our unsatisfactory performance in the first year of the audit and more importantly focuses on what we are doing to improve the service we deliver. Disclosures: O. Wade None. J. Loh None. J. Withers None. S. Fish None. E. MacPhie Other; EM is the secretary of the North West Rheumatology Club; meetings are supported by an unrestricted educational grant from UCB.